1982
DOI: 10.1038/bjc.1982.294
|View full text |Cite
|
Sign up to set email alerts
|

A biochemical and immunohistological study of collagen synthesis in Ewing's tumour

Abstract: Summary.-The synthesis and localization of collagen have been studied on material from a total of 16 primary Ewing's tumours. The predominant collagen extracted from the tissues and synthesized in short-term cultures was type I. The proportion of type III collagen was relatively small and variable (0-8%) in the direct tumour extracts, but a higher proportion (29-38% of the total collagens) was synthesized in culture. Immunofluorescence studies showed that positive staining for all types of collagen tested (typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Interestingly, in two different ES cell lines, derived from the same patients, a 2 b 1 was higher on primary cells compared with metastatic cells (vanValen et al, 1994). This may reflect the fact that the predominant collagen extracted from ES tissue and synthesized in short-term cultures is type I (Harvey et al, 1982). Therefore, cells lacking a 2 b 1 are less facilitated to have stable anchorage to the ECM in ES tissue and may have increased migratory abilities.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, in two different ES cell lines, derived from the same patients, a 2 b 1 was higher on primary cells compared with metastatic cells (vanValen et al, 1994). This may reflect the fact that the predominant collagen extracted from ES tissue and synthesized in short-term cultures is type I (Harvey et al, 1982). Therefore, cells lacking a 2 b 1 are less facilitated to have stable anchorage to the ECM in ES tissue and may have increased migratory abilities.…”
Section: Discussionmentioning
confidence: 92%
“…The contribution of ECM remodeling to growth and progression of EwS has not been deeply investigated, though clinico-pathologic correlative studies suggested that a stroma-rich TME influences EwS gene expression and patient prognosis (45). EwS cells and tumors can deposit fibrillar and non-fibrillar proteins (46)(47)(48) and we previously showed that activation of canonical Wnt/beta-catenin and TGF-beta signaling upregulates secretion of pro-tumorigenic andangiogenic matrisomal proteins by EwS cells, including collagens and TNC (49,50). In the current work, we have identified discrete subpopulations of EwS cells that deposit protumorigenic ECM proteins in vivo.…”
Section: Discussionmentioning
confidence: 99%